Training in the fasted state facilitates re-activation of eEF2 activity during recovery from endurance exercise - van Proeyen, K.; de Bock, K.; Hespel, P. (European Journal of Applied Physiology, 2011)
Nutrition is an important co-factor in exercise-induced training adaptations in muscle. We compared the effect of 6 weeks endurance training (3 days/week, 1-2 h at 75% VO2peak) in either the fasted state (F; n = 10) or in the high carbohydrate state (CHO, n = 10), on Ca2+-dependent intramyocellular signalling in young male volunteers. Subjects in CHO received a carbohydrate-rich breakfast before each training session, as well as ingested carbohydrates during exercise. Before (pretest) and after (posttest) the training period, subjects performed a 2 h constant-load exercise bout (~70% of pretest VO2peak) while ingesting carbohydrates (1 g/kg/h). A muscle biopsy was taken from m. vastus lateralis immediately before and after the test, and after 4 h of recovery. Compared with pretest, in the posttest basal eukaryotic elongation factor 2 (eEF2) phosphorylation was elevated in CHO (P < 0.05), but not in F. In the pretest, exercise increased the degree of eEF2 phosphorylation about twofold (P < 0.05), and values returned to baseline within the 4 h recovery period in each group. However, in the posttest dephosphorylation of eEF2 was negated after recovery in CHO, but not in F. Independent of the dietary condition training enhanced the basal phosphorylation status of Phospholamban at Thr17, 5´-AMP-activated protein kinase a (AMPKa), and Acetyl CoA carboxylase b (ACCb), and abolished the exercise-induced increase of AMPKa and ACCb (P < 0.05). In conclusion, training in the fasted state, compared with identical training with ample carbohydrate intake, facilitates post-exercise dephosphorylation of eEF2. This may contribute to rapid re-activation of muscle protein translation following endurance exercise.